I feel proud why do I feel proud today! (London Dorling Kindersley Limited, 2020)
I Feel Proud encourages children to embrace their talents and grow their confidence from an early age. This colorful board book provides a starting point for children to reflect on what they are proud of, whether it's a baby sibling or an amazing drawing. It also warns against the dangers of being overly confident and diminishing the achievements of other people, helping young children develop this important life skill
Linguistic notions
2
Keywords: Board books; Confidence -- Pictorial works -- Juvenile literature; Emotions -- Pictorial works -- Juvenile literature